(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Beauty filters are widely used on social media platforms, and while they enhance appearance, they can also lead to negative psychological outcomes. Research has shown that exposure to unrealistic beauty standards can contribute to the development of body dissatisfaction, low self-esteem, and negative body image. Furthermore, the use of beauty filters can perpetuate the idea that physical attractiveness is the most important factor in social acceptance and success, which can lead to feelings of inadequacy and anxiety. As a result, there is a need for further research to understand the potential long-term consequences of beauty filters on mental health and to develop strategies to minimize their negative effect. The majority of respondents aged eighteen to twenty (18-20) believed that social media filters have a psychological impact. Individual variations affect these age groups the most, and they are more attentive and aware of the impact of their surroundings, particularly social factors. Social media filters, in general, are growing increasingly popular because they enable users to represent certain personalities and characters, generate creative content, and improve self- confidence. Nevertheless, using filters can create the illusion of digital beauty, in which users compare their looks to artificial standards, leading to a loss of confidence in real life. Users’ expectations of how they should appear may shift as they spend more time on social media. This view implies that individuals are typically satisfied with their looks, whether or not they utilize digital filters. Their total composite emotional impact average was four (4), suggesting that the person is typically satisfied and confident in their looks, regardless of whether they utilize digital filters.